PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA SUAP DALAM TINDAK PIDANA KORUPSI - Hidayat , (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2017)
The eradication of corruption could not be easy as assumed generally to do because of the system of government so far never priores the transparency and reliability vertically on primordialism which use the recruitment system, mutation and promotion on the base of nepotism to family, same of ethnic, and motion of political repayment. Kata Kunci : Korupsi, Suap, Pertanggungjawaban Pidana